Murine Models for Staphylococcal Infection. Issue 3 (3rd March 2021) - Klopfenstein, Nathan; Cassat, James E.; Monteith, Andrew; Miller, Anderson; Drury, Sydney; Skaar, Eric; Serezani, C. Henrique
Abstract: Staphylococcus aureus is a Gram‐positive bacterium that colonizes almost every organ in humans and mice and is a leading cause of diseases worldwide. S. aureus infections can be challenging to treat due to widespread antibiotic resistance and their ability to cause tissue damage. The primary modes of transmission of S. aureus are via direct contact with a colonized or infected individual or invasive spread from a colonization niche in the same individual. S. aureus can cause a myriad of diseases, including skin and soft tissue infections (SSTIs), osteomyelitis, pneumonia, endocarditis, and sepsis. S. aureus infection is characterized by the formation of purulent lesions known as abscesses, which are rich in live and dead neutrophils, macrophages, and surrounded by a capsule containing fibrin and collagen. Different strains of S. aureus produce varying amounts of toxins that evade and/or elicit immune responses. Therefore, animal models of S. aureus infection provide a unique opportunity to understand the dynamics of organ‐specific immune responses and modifications in the pathogen that could favor the establishment of the pathogen. With advances in in vivo imaging of fluorescent transgenic mice, combined with fluorescent/bioluminescent bacteria, we can use mouse models to better understand the immune response to these types of infections. By understanding the host and bacterial dynamics within various organ systems, we can develop therapeutics to eliminate these pathogens. This module describes in vivo mouse models of both local and systemic S. aureus infection. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Murine model of Staphylococcus aureus subcutaneous infection Alternate Protocol : Murine tape stripping skin infection model Basic Protocol 2 : Sample collection to determine skin structure, production of inflammatory mediators, and bacterial load Basic Protocol 3 : Murine model of post‐traumatic Staphylococcus aureus osteomyelitis Basic Protocol 4 : Intravenous infection of the retro‐orbital sinus Support Protocol : Preparation of the bacterial inoculum